How much plastic have you drunk today? - Grayson, T. (2020)
Worldwide, one in three people do not have access to safe drinking water [1], resulting in the deaths of nearly 1000 children every day. Standard tests can take several days to produce a result [2], by which time it is often too late since the contaminated and polluted water has already been used. Hence, there is a clear need for rapid and specific testing that can produce results in real time. Here, we focus on microplastics pollution in drinking water. A typical pollution pathway is shown in Fig. 1 [3].